2001
DOI: 10.1017/s0033291701003282
|View full text |Cite
|
Sign up to set email alerts
|

Chronic aircraft noise exposure, stress responses, mental health and cognitive performance in school children

Abstract: Background. Previous research suggests that children are a high risk group vulnerable to the effects of chronic noise exposure. However, questions remain about the nature of the noise effects and the underlying causal mechanisms. This study addresses the effects of aircraft noise exposure on children around London Heathrow airport, in terms of stress responses, mental health and cognitive performance. The research also focuses on the underlying causal mechanisms contributing to the cognitive effects and potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
216
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(232 citation statements)
references
References 31 publications
11
216
0
5
Order By: Relevance
“…In visible test, there was no significant difference between LI and HI. This finding is similar to Hamberick-Dixon's [13] interpretation that they did not find different effects of noisy and quiet day care center in separation of relevant visual cues, because of directing the subjects to pay more attention to visual rather than auditory resources [13,23]. Also this is in agreement with Glass and Singer's [16] findings that found the psychological and behavioral adaptation to brief noise exposure.…”
Section: Discussionsupporting
confidence: 90%
“…In visible test, there was no significant difference between LI and HI. This finding is similar to Hamberick-Dixon's [13] interpretation that they did not find different effects of noisy and quiet day care center in separation of relevant visual cues, because of directing the subjects to pay more attention to visual rather than auditory resources [13,23]. Also this is in agreement with Glass and Singer's [16] findings that found the psychological and behavioral adaptation to brief noise exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Deleterious effects of noise on various cognitive abilities among adults, such as short-term or long-term memory and mental health, have been demonstrated in previous studies [1][2][3][4] . Exposure to environmental noise was also found to impair a number of cognitive parameters among children [5][6][7] . Recently, Clark et al established the adverse effect of chronic aircraft and road traffic noise exposure on reading comprehension among primary school children 8) .…”
mentioning
confidence: 99%
“…2 This study suggests that the three predominant hypotheses; psychosocial stressors, concentrated 3 disadvantage and selective migration, only partially explain the association between cities and poor 4 mental health. Other possible explanations that have been gaining impetus recently include levels 5 of air or noise pollution (Haines et al, 2001;WHO, 2014a), reduced access to green space (Lee and 6 Maheswaran, 2011), or reduced levels of social support (DeSilva, 2005). A recent study found that 7 living close to an urban park had the same mental health benefits as decreasing local unemployment 8 rates by 2 percentage points, suggesting at least the potential of environmental interventions to 9 improve population mental health (Sturm and Cohen, 2014).…”
Section: Discussion 34mentioning
confidence: 99%